Effectiveness of Counseling with Booklet Media on Improving Pregnant Women's Knowledge about Gingivitis at Kedungmundu Public Health Center in Semarang City - Issanti, Syifa Rachma; Kurnia Dewi, Maria Ulfah; Kusniati, Retno (Jurnal Kesehatan Gigi, 2023)
Introduction: Gingivitis is referred to as an oral manifestation in pregnant women and occurs around 30-100%. The main causative factor for gingivitis is plaque, supported by an increase in pregnancy hormones, as well as a lack of knowledge. These problems can cause risks to both pregnant women and the fetus if they are not immediately followed up. Objective: To analyze the effectiveness of counseling using booklet media on increasing pregnant women's knowledge about gingivitis at Puskesmas Kedungmundu, Semarang City. Method: Quasi experiment with non equivalent control group design. The sampling method is non-probability sampling with a Â consecutive sampling technique using the Taro Yamane formula. Results: Test the hypothesis with paired t test and independent t test. The sample size obtained was 60 people, with the knowledge category before counseling the experimental group was 33.3% good, 23.3% sufficient, and 43.3% lacking. After counseling using booklet media, the results of the post test showed a good knowledge category of 60%, 16.7% sufficient, and 23.3% lacking. The effect of booklet media counseling on the knowledge of pregnant women with a p-value of 0,001 (p <0,05). Conclusion: Counseling using booklet media is effective for increasing pregnant women's knowledge about gingivitis at Puskesmas Kedungmundu, Semarang City.